Analysis of Chlorophyll-Screwpine (Pandanus amaryllifolius) Interaction with Bawang Dayak (Eleutherine sp.) via UV-Vis - Manurung, Tety Wahyuningsih; Pasaribu, Marvin Horale; Ariefin, Mokhamat; Hakim, Muh. Supwatul; Zahra, Laila; Alfanaar, Rokiy (Jurnal Teknologi Pangan, 2025)
The use of natural pigments, both in the food and cosmetic industries, is gaining popularity due to their environmentally friendly nature and minimal health risks. One natural pigment that is often used is chlorophyll, a color pigment that provides a distinctive green color and is beneficial for health. However, the interaction of chlorophyll when interacting with other bioactive compounds is still poorly studied.  This study aims to analyze the interaction between chlorophyll from skrewpine leaves (Pandanus amaryllifolius) with bioactive compounds from dayak onions (Eleutherine sp.) using UV-Vis spectroscopy. through mixing extracts with various volumes. The results of UV-Vis analysis showed absorption in the 420 nm and 670 nm regions which showed typical absorption of chlorophyll. These absorbances did not show significant differences in the addition of Eleutherine sp. extracts in various volume ratios. Which indicates that there are no significant interactions or reactions that can degrade chlorophyll in Eleutherine sp. secondary metabolites. However, color analysis based on RGB and CIE LAB shows significant differences.